HISTORICAL EVIDENCE OF TUHK MANUK SANCTUARIES UNTIL THE SECOND HALF OF THE 19th CENTURY - Ogannisan, Karen Oganesovic (History, Archeology and Ethnography of the Caucasus, 2023)
The article is devoted to the folk sanctuaries Tukh Manuk widespread in the Republic of Armenia (as well as in the territory of historical Armenia). The article considers only those Tukh Manuk sanctuaries mentions of which are available in thet sources dating before the second half of the 19th century, for that is important taking note of numerous speculations on the pre-Christian origin of these sanctuaries. It is the extremely meager data of ancient historical information that makes such speculations possible. Our research on this topic indicates mentioning of Tukh Manuk not earlier than the end of the 14th century, either as names of convents and churches, or as personal names. Proceeding from this, it is possible to “ancientize” the Tukh Manuk sanctuaries for a couple of centuries, but there is no way to ascribe them to pre-Christian times. All Tukh Manuk shrines listed in this article are somehow connected with the Holy Signs or Holy Crosses, relics related to Jesus Christ. Thus, it can be said that Tukh Manuk was once associated with the popular cult of Christ. One of the folk legends recorded in the 19th c. points directly to Christ. Since the second part of the 19th c., references to these sanctuaries have increased dramatically and numerous folklore materials have also been recorded, which makes it possible to study these sanctuaries in more detail. After 1828, Tukh Manuk sanctuaries appeared in large numbers in Eastern Armenia due to internal migration and forced resettlement, when the people moved and took their sacral objects along with them. The distribution geography of the Tukh Manuk sanctuaries is an important additional source for understanding the directions of internal migration and forced resettlement in historical Armenia.